2014
DOI: 10.1002/btpr.1882
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effect of triton X‐114 on the physicochemical properties of an antibody fragment

Abstract: The effect of Triton X-114 on the physicochemical properties of a single-chain antibody fragment (scFv) has been studied. According to the far UV circular dichroism spectroscopy, the secondary structure of the recombinant antibody was not significantly affected by the presence of Triton. From the antibody tertiary structure analysis, it was found that the surfactant could be located around the tryptophan molecules accessible to the solvent, diminishing the polarity of its environment but maintaining most of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(96 reference statements)
2
4
0
Order By: Relevance
“…This behavior evidences the water soluble character of most of proteins present in the broth supernatant, including the scFv molecule. Moreover, it agrees with our previous works which demonstrated that scFv relative surface hydrophobicity was similar to that of hydrophilic model proteins [37].…”
Section: Effect Of Additivessupporting
confidence: 92%
See 1 more Smart Citation
“…This behavior evidences the water soluble character of most of proteins present in the broth supernatant, including the scFv molecule. Moreover, it agrees with our previous works which demonstrated that scFv relative surface hydrophobicity was similar to that of hydrophilic model proteins [37].…”
Section: Effect Of Additivessupporting
confidence: 92%
“…Solutions of Triton X-114 4% wt/wt and a temperature of 24 °C were selected as working conditions to ensure phase separation in all the assayed systems. According to previous works, scFv structure was demonstrated to be unaffected by the selected surfactant at room temperature [37].…”
Section: Protein Partitioningmentioning
confidence: 88%
“…According to our preliminary results, scFv was concentrated and partially purified in a single extractive step with recovery percentages superior to 80% and purification factors of approximately 2 [30]. Even though these results were similar or even better than those reported for other authors [30,31], a further improving of this purification performance would be desirable, thus requiring the application of statistical techniques.…”
Section: Introductionsupporting
confidence: 60%
“…An apparent disadvantage of this methodology is that the target protein, scFv, is recovered in a surfactant (Triton X-114)-enriched phase. However, it was already demonstrated that working at temperatures of approximately 17 °C, the used surfactant does not significantly modify the protein structure and stability [31]. Besides, when a further purification grade of scFv is required, the obtained sample is able to be applied in other additional separation processes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The highest peptide content (p < 0.05) was observed for the soy flour treated with liquid-liquid extraction. This fact could be a consequence of different processes such as the reduction of protease inhibitors, which result in a higher enzymatic M A N U S C R I P T A C C E P T E D activity (Capriotti et al, 2015) or the increase in the exposure of inner amino acids, derived from the preferential interaction between hydrophobic patches of soy proteins and the surfactant (Malpiedi, Nerli, Abdalla, & Pessoa, 2014).…”
Section: In Vitro Gastrointestinal Digestionmentioning
confidence: 99%